Effects of woody vegetation on shallow soil moisture at a semiarid montane catchment. Issue 5 (15th August 2014) - Traff, Devin C.; Niemann, Jeffrey D.; Middlekauff, Stephen A.; Lehman, Brandon M.; Boudell, Jere A.; Dixon, Mark D.; Rood, Stewart B.; Stromberg, Juliet C.
Abstract In semiarid montane regions, spatial patterns of shallow soil moisture (0–5 cm) are expected to depend on vegetation patterns and topographic attributes. In some cases, the vegetation patterns themselves depend on the topography, which makes the interaction of soil moisture, vegetation and topography especially complex. Such is the case in portions of the Colorado Front Range where many south‐facing and north‐facing slopes are primarily vegetated by mountain mahogany (Cercocarpus montanus) shrubs and ponderosa pine (Pinus ponderosa) trees, respectively. The objectives of this paper are the following: (1) to determine how the presence of a shrub or tree affects the shallow soil moisture on these distinct hillslopes and (2) to understand the main mechanisms through which the vegetation affects the shallow soil moisture. On opposing hillslopes in the Cache la Poudre catchment, soil moisture was monitored for intercanopy, shrub canopy and tree canopy locations. Throughfall, insolation, soil texture and hydrophobicity were also measured to understand the reasons for any soil moisture differences. The results suggest that the shallow soil moisture is more distinct between the canopy and intercanopy locations on the south‐facing slope than the north‐facing slope. On the south‐facing slope, intercanopy locations are less shaded by the nearby canopy because of the shorter stature of the shrubs and the orientation of this hillslope towards the sun. Copyright © 2014 John Wiley & Sons, Ltd.